Managerial Readiness Model of Islamic Philanthropic Institutions in Disaster Management Based on Maqāṣid al-Syarī‘ah - Icha afrillia Hidayat; Femei Purnamasari; Fatih Fuadi (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
Indonesia is a country with a high level of disaster vulnerability, thus requiring an integrated disaster management system involving various parties, including Islamic philanthropic institutions. Islamic philanthropic institutions have great potential through the management of zakat, infaq, sedekah, and waqf (ZISWAF) funds to support mitigation, emergency response, and post-disaster recovery. However, in practice, various managerial obstacles remain, such as weak strategic planning, institutional coordination, and monitoring and accountability systems. This study aims to formulate a model of managerial readiness of Islamic philanthropic institutions based on Maqāṣid al-Syarī‘ah in disaster management. The study uses a qualitative approach with library research methods. Data were obtained from books, journal articles, research reports, and official documents related to Islamic philanthropy, disaster management, and Maqāṣid al-Syarī‘ah. Data analysis was carried out through data reduction, theme categorization, and conceptual synthesis. The results of the study indicate that managerial readiness can be built through the integration of modern management functions with the five dimensions of Maqāṣid al-Syarī‘ah, namely ḥifẓ al-dīn, ḥifẓ al-nafs, ḥifẓ al-‘aql, ḥifẓ al-nasl, and ḥifẓ al-māl. This integration is realized in planning based on life and spiritual protection, organizing through strengthening human resource capacity, implementing programs oriented towards protecting vulnerable groups, and supervision that emphasizes transparency and accountability in the management of ZISWAF funds. Thus, the managerial readiness model based on Maqāṣid al-Syarī‘ah is able to strengthen the professionalism of Islamic philanthropic institutions while providing disaster management that is more effective, sustainable, and oriented towards the welfare of the community.